A revised classification of temperate lowland groundwater‐fed headwater streams based on their flora. (30th March 2020) - Westwood, Christian G.; England, Judy; Johns, Tim; Stubbington, Rachel
Abstract: Prolonged drought leads to the temporary simplification or loss of aquatic biological communities, as surface water is progressively reduced or dry phases are extended in intermittent streams. Using surveys of aquatic and semi‐aquatic plants, and recording non‐aquatic grasses and herbs, we classify the communities within 24 groundwater‐fed streams in south England. We examine changes over a 21‐year period following a 3‐year drought. Our classification reveals a simplification of communities driven by a decline in the abundance of obligate aquatic taxa and an increase in the abundance of semi‐aquatic taxa. We demonstrate plant community structure as a strong indicator of a site's flow history, including intermittence, but interactions with channel morphology also influence communities and need further investigation. We recommend that future surveys encompass terrestrial, semi‐aquatic and aquatic plants, as well as habitat assessments, to improve the understanding of how instream communities change between flowing, ponded and dry phases in intermittent streams.